PERSUASIVE COMMUNICATION STRATEGIES OF THE SEMARANG CITY DEVELOPMENT PLANNING AGENCY (BAPPEDA) IN THE “KITA TANI MUDA” PROGRAM - Yudianisa, Rahma; Luqman, Yanuar (International Journal of Cultural and Social Science, 2026)
Facing a decline in farmers and limited agricultural land, the Semarang City Development Planning Agency (Bappeda Kota Semarang) launched "Kita Tani Muda," a business incubation program to attract young generation’s participation to agriculture. Although Bappeda Kota Semarang promoted the program through various channels, it failed to meet its target number of participant. The main objective of this study is to understand the persuasive communication carried out by Bappeda Kota Semarang in promoting the Kita Tani Muda program by analyzing the communication elements contained within it. This study also identifies factors that hinder the community from participating in Kita Tani Muda. This study used a qualitative method with a case study approach. The results show that Bappeda Kota Semarang has carried out persuasive communication in promoting Kita Tani Muda by establishing source credibility, designing attractive messages, and selecting relevant channels. However, participants were hesitant to join due to their unfamiliarity with the concept of business incubation and its benefits. The study concludes that Bappeda Kota Semarang needs to enhance public awareness of business incubation and create more effective promotional strategies to boost participation in similar programs in the future.